ChemInform Abstract: Pd(OAc)2 Without Added Ligand as an Active Catalyst for Mizoroki—Heck Reaction in Aqueous Media. Issue 17 (4th April 2013) - Amini, Mojtaba; Bagherzadeh, Mojtaba; Moradi‐Shoeili, Zeinab; Boghaei, Davar M.
Abstract The present new method provides internal E‐isomers exclusively, except the reaction with acrylonitrile (IV) gives a mixture of stereoisomers.